Peculiar features of the clinical course of reflux disease in diabetic patients - Natalya Vyacheslavovna Korneeva; Yury Leonidovich Fedorchenko (Сахарный диабет)
Aim. To elucidate peculiar features of the clinical course of gastroesophageal reflux disease (GERD) in patients with type 1 and 2 diabetes mellitus(DM1 and DM2). Materials and methods. The study included 258 patients (68 DM and 190 DM2) undergoing 24-hour pH-metry, gastric and oesophageal endoscopy,and evaluation of H.pylori (Hp) infestation. Results. Based on the results of pH-metry and complaints of the patients, GERD was diagnosed in 23.5 and 33.6% of DM1 and DM2 patients respectively.GERD in DM patients is frequently asymptomatic, with fewer complaints of oesophageal problems but more pronounced endoscopic changesin patients with GERD alone. Patients with GERD + DM more frequently present with erosive oesophagitis and oesophageal ulcers than those withGERD without DM. Patients with GERD + DM are characterized by a higher occurrence of H.pylori in gastric mucosa than patients with DM alone. Conclusion. GERD is a frequent pathology in DM1 and DM1 patients characterized by a peculiar, frequently asymptotic, clinical course; it requiresthorough attention of endocrinologists and gastroenterologists.